A cláusula de raio nos contratos de locação em shopping center - Volani, Luiz Felipe Sousa Leão (2015)
The objective of this study is to present a review of literature on the radius clause in the lease atypical contracts in shopping center, with emphasis on the fact whether such a clause should be or not regulated by law, against the recent decision by CADE. The study based on a literature search in the doctrine and jurisprudence cork country theme. The radius clause, also known as territorial exclusivity clause summarized as that by which the lessee of a commercial space undertakes before the lessor, from pursuing activities similar to practice in the leased property in another establishment in a certain radius away from that property. It concluded that the radius clause should not be regulated by specific law or the Civil Code, shall be at the discretion of the parties involved in the contract to establish what are the rules and extent of territoriality, based on good faith objective, common sense, market research, time limit, space, among others